👤

Efectuati:
a. [tex]( - \frac{7}{11} ) + ( - \frac{2}{33} ) : \frac{8}{3} [/tex]
b. [tex]( - \frac{3}{8} - \frac{1}{8} : \frac{3}{4} ) : ( + \frac{13}{8} )[/tex]


Răspuns :

a).    *   efectuam impartirea ... -2/33 * 3/8 = - 1/11*1/4 = -1/44  
                                                                                      (am simplificat cu 2 si 3) ;
       **   efectuam adunarea ... - 7/11 + (-1/44) = - (7*4+1)/44 = - 29/44 ;
b).   *   -1/8 : 3/4 = -1/8 * 4/3 = - 1/6    (la 8 si 4 am simplificat cu 4 )
      **    (...)= - 3/8 - 1/6 = - (3*3+1*4)/24 = - 13/24 ;
     ***    ... = - 13/24 * 8/13 = - 1 / 3  (am simplificat cu 8 respectiv 13 )